HCV Genotype-1 Subtypes and Resistance-Associated Substitutions in Drug-Naive and in Direct-Acting Antiviral Treatment Failure Patients. Issue 5 (July 2017) - Gozlan, Yael; Ben-Ari, Ziv; Moscona, Roy; Shirazi, Rachel; Rakovsky, Aviya; Kabat, Arij; Veizman, Ella; Berdichevski, Tania; Weiss, Peretz; Cohen-Ezra, Oranit; Lurie, Yoav; Gafanovich, Inna; et al.
Background: Direct-acting antiviral (DAA) treatment regimens and response rates of patients with HCV genotype-1 (GT1) are currently considered subtype-dependent. Identification of clinically relevant resistance-associated substitutions (RASs) in the NS3 and NS5A proteins at baseline and in DAA failures, may also impact clinical decisions. Methods: In a multicentre cohort study ( n =308), NS3 or NS5B sequencing ( n =248) was used to discriminate between GT1 subtypes. The correlation between baseline NS3 and NS5A RASs on the 12-week sustained virological response (SVR12) rates of 160 of the patients treated with second-generation DAAs was also assessed. Post-treatment resistance analysis was performed on samples from 58 patients exhibiting DAA virological failure. Results: GT1a, GT1b and GT1d subtypes were identified in 23.0%, 75.4% and 1.2% of tested samples. GT1b was most prevalent (97.7%, 128/131) among patients born in the former Soviet Union. The Q80K NS3 RAS was identified in 17.5% (10/57) of the GT1a carriers, most of whom were Israeli-born. NS3 and NS5A baseline RASs showed a negligible correlation with SVR12 rates. Treatment-emergent RASs were observed among 8.9% (4/45) and 76.9% (10/13) of first- and second-generation DAA failures, respectively, with D168V/E (NS3), Y93H and L31M (NS5A) being the most prevalent mutations. Conclusions: NS3 sequencing analysis can successfully discriminate between GT1 subtypes and identify NS3 amino acid substitutions. While pre-treatment NS3 and NS5A RASs marginally affect second-generation DAA SVR12 rates, post-treatment resistance analysis should be considered prior to re-therapy.